“Thank you, God-pleasing ones”: the ministry of church singers of the Perm diocese in the second half of the 1960s — early 1980s - Sapsay Andrey, Archpriest (Вестник Свято-Филаретовского института)
This article is devoted to the study of the activities of church singers in the Perm region in the 1960s and 1980s. Having used archival documents, the author provides data on the number of the church singers, their age, education, social status and level of financial support. It is noted that the church singers’ activities were attentively monitored by the local authorities. Thus, the commissioners of the Council for Religious Affairs limited the number of the singers, prevented the admission of young people to choirs, demanded certificates from their main place of work authorizing them to combine it with church singing, and exerted pressure on them through the Soviet party organs and the media. It was found that the leadership of the Perm diocese made special efforts to improve liturgical singing in the churches. Singers with musical education were invited to replace amateur singers in the church choirs, and parish expenses for choirs were regularly increased. In the early 1980s, after the weakening of ideological influence, a gradual revival of church singing in parishes began. Thanks to the memoirs of Archimandrite Lev (Akhidov), singers V. D. Deryusheva and N. M. Dyldina, the author managed to compile a complete picture of historical events on this subject.